Unicameral bone cyst of the patella in a young dog - Petazzoni, M.; Briotti, F.; Beale, B. (Veterinary and Comparative Orthopaedics and Traumatology, 2015)
This report describes a case of a solitary unicameral patellar bone cyst in a young dog. A five-month-old, male Dobermann Pinscher dog was referred for a 10-day left hindlimb lameness. A mild swelling of the peripatellar soft tissues of the left patella was detected upon physical examination. Signs of pain were elicited upon direct palpation of the patella. Radiographic examination revealed an oval radiolucency within the medullary cavity at the base of the left patella. Radiographic examination, arthroscopy, and histopathology findings supported the diagnosis of a benign patellar bone cyst. The condition was treated by surgical curettage and autogenous bone graft harvested from the ipsilateral proximal tibia. Clinical signs, including lameness and signs of pain upon deep palpation, disappeared three weeks after surgery. Follow-up re-evaluation five years after surgery revealed no recurrence of the cyst and the patient was asymptomatic.
Keywords: Patella; bone; cyst; dog; canine